Analisis Peranan Guru Kelas dalam Membina Budi Pekerti Siswa di Sekolah Dasar Islam Terpadu Arrahmah Depok - Nur Hikmah; Ade Wijaya; Dadang Kurnia; Syarif Hidayatullah (Tematik: Jurnal Penelitian Pendidikan Dasar, 2022)
The research used is a qualitative method with a descriptive approach. The research was conducted at SDIT Arrahmah Depok City, West Java, Indonesia. Of the total population of students in grade IV and V totaling 50 people, the samples taken were 30 students from class V. The method of collecting research data in the field uses a survey method while the statistical method of data analysis uses quantitative data techniques, frequency distribution, and data interpretation. Based on the calculation results, the research results obtained are: that 7 people (23.33%) from 30 students of SD Islam Terpadu Arrahmah Depok stated that the Role of Classroom Teachers was categorized as having a high Role, namely in the range of 57 to 63, 17 people (56.67%) of students stated that the role of the classroom teacher was included in the category of having a moderate role. This can be seen from the respondents 'answers in the score range 29 to 56, while as many as 6 students (20.00%) students stated that the Role of Classroom Teachers was included in the category of having a low Role, seen from the respondents' answers in the range of 22 to 28. Based on the results According to the calculation above, it can be concluded that the role of the classroom teacher in building character at SDIT Arrahmah which is done in the Medium category or in other words is Good.